Analisis Pengaruh Gaya Kepemimpinan dan Komitmen Organisasi terhadap Pengembangan Karir Karyawan pada PT. Agung Automall Cabang Bengkulu - Sri Ekowati; Tezar Arianto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of leadership style and organizational commitment on employee career development at PT. Agung Automall Bengkulu Branch. The sample in this study was 100 employees of PT. Agung Automall Bengkulu Branch and has become a permanent employee. because all the populations in this study were sampled, the sampling method was saturated or census. The analysis technique used is multiple linear regression, coefficient of determination, and hypothesis testing. The results showed that the leadership style had an effect on career development at PT Agung Automall Bengkulu Branch, meaning that the better the leadership style, the career development of employees at PT. Agung Automall Bengkulu Branch will continue to increase. Organizational commitment has an effect on career development at PT Agung Automall Bengkulu Branch, meaning that the more employee organizational commitment increases, the career development of employees at PT. Agung Automall Bengkulu Branch will continue to increase.